Efforts of Islamic Education Teachers in Preventing Students Delinquency at SMP Bina Insan Mandiri Nganjuk - Hefni Hefni (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2017)
This article examines the efforts of Islamic Education Teachers in preventing juvenile delinquency. Teachers are people who interact directly with students. This shows that PAI teachers have a major influence in preventing student delinquency and shaping the personality of the Islamic students. This research revealed the forms of student delinquency, causes, and efforts made PAI teachers in preventing student delinquency at SMP Bina Insan Mandiri Nganjuk. This research uses qualitative method with descriptive approach. Sampling technique used was purposive sampling and snowball sampling. The data collection methods were direct interview, field observation and documentation. The results showed that students' misbehavior varied, including students often arrived late, truancy, not doing tasks, dating, getting along with students who are not muhrim, untidy dresses. The causes are that they mischoose their daily interaction, less supportive environment, busy parents, quarreling, loving more worlds, worse communication with children. Efforts made by PAI teachers are arranging school rules and educational sanctions, controlling student activities, personal and jama'ah coaching, motivating every religious activity, visiting abusive student homes, establishing good communication with parents, giving advice, modeling and familiarizing students with good deeds.